Indication for treatment and severity of disease in treatment-naive patients with chronic hepatitis B virus infection. Issue 6 (June 2019) - Post, Gerrit; Shalev, Noga; Baumgarten, Axel; Shimakawa, Yusuke; Lemoine, Maud; Krznaric, Ivanka; Dupke, Stephan; Carganico, Andreas; Arastéh, Keikawus; Ingiliz, Patrick
Abstract : Background and aims: The prevalence of chronic hepatitis B virus (HBV) infection in Europe is poorly defined. Data on the proportion of patients eligible for therapy are lacking but are crucial to meet WHO elimination goals. The aims of our study were to provide an estimate of the need for antiviral treatment and to assess the prevalence of advanced liver disease in treatment-naive, chronic HBV-infected patients. Patients and methods: We performed a retrospective, cross-sectional analysis of all treatment-naive HBV-infected patients. Baseline clinical assessments included sociodemographic data, hepatitis B-specific analyses, and liver stiffness measurement (LSM). Results: Between 2010 and 2017, 465 patients with chronic HBV infection were referred, with 301 (64.7%) being eligible for our analysis. Overall, 40% were female, and the mean age was 39.3±13.1 years. Moreover, 61% of patients were born outside Europe, predominantly in the Asia-Pacific region. The median HBV viral load was 1630 IU/ml (interquartile range: 240–35 000 IU/ml), 145 (48.2%) patients had an HBV viral load above 2000 IU/ml, and 14.3% were HBeAg positive. Median LSM was 5.2 kPa (interquartile range: 4.2–6.6 kPa). LSM indicating clinically significant fibrosis (≥F2) was found in 96/271 (35.0%) patients, including 20/271 (7.4%) patients with suspected advanced fibrosis/cirrhosis. Overall, 26% of patients met EASL 2017 treatment criteria. Conclusion: In HBV-infected patients referred to one of the largest ID clinics in Berlin, only 26% met EASL treatment criteria and 7% had suspected cirrhosis at presentation. Only in 4% of all patients, a treatment indication could not be determined by a noninvasive approach.